OPTIMALISASI PERAWATAN SEKOCI PENOLONG GUNA MENUNJANG KESELAMATAN JIWA DI LAUT PADA KM. EGON - Rahman Aulia, Akram; Ali Mashartanto, Achmad; Yudho Baskoro, Bayu; Efrianto, Dody; Abadi, Kurniawan (STKIP Subang, 2026)
Lifeboat maintenance is crucial. This study aims to optimize lifeboat maintenance on the KM. Egon ship. This study uses descriptive qualitative research with data collection techniques including field observation, interviews, and documentation studies. The results indicate that obstacles to lifeboat maintenance on the KM. Egon ship are influenced by several factors: maintenance schedules, human factors, material factors, and weather factors. This effort was made based on data obtained by the author during sea practice on the KM. Egon addresses these issues by establishing a lifeboat maintenance schedule aligned with loading and unloading schedules, distributing tasks among crew members, conducting regular safety meetings, and maintaining lifeboats in accordance with applicable SOPs. These SOPs are also conducted to ensure there are no issues during drills or emergencies. With these efforts, it is hoped that the lifeboats onboard the KM. Egon will be better maintained, minimizing damage or problems during operation.